Tema dan isu penyelidikan mengenai gejala sosial pada dekad pertama abad 21 di Malaysia. - Azlina Abdullah, (Universiti Kebangsaan Malaysia, 2010)
Malaysia is striving to become a developed nation by 2020. However, such development and progress have also brought about many problems in society that require the scholars, thinkers and policy makers to seek ways to effectively address them. The increase in crimes and other social problems such as murder, robbery, rape, domestic violence, drug addiction, snatching, extra-marital sex, and internet pornography, have caused grave concern regarding security among members of society, foreign tourists and investors. Researchers have conducted many studies on these social problems. In fact for the period since the beginning of this decade, about 150 studies have been conducted on social problems. Most of the studies consisted of basic or applied research and studies for the fulfillment of the Masters and PhD theses, while consultancy research for policy input were very few. In terms of issues analysed, these studies focused more on statistics and types of crimes, as well as on common social problems such as incest, misdemeanour among school students, illegal racing, and internet pornography. Studies on serious crimes such as murder, armed robbery and syndicated crimes that would have serious impact on security and welfare of society are extremely few. Given such a situation, new studies especially those that could provide input to policy should be given priority in the country’s social development policy. Research and development especially in the field of social sciences and humanities should contribute to the corpus of knowledge, but equally important is public advocacy to help policy formulation for the well-being of the country and society.